Lingkungan Positif dalam Mendukung Pembelajaran - Habsy, Bakhrudin All; Shidqah, Syafira Badhiatus; Amali, Azzah Nabila; Fadhilla, Intan Nur (TSAQOFAH, 2024)
A positive environment can greatly support individual learning and growth. Whether it is in the context of formal education, professional training, or lifelong learning, a supportive environment plays a very important role. Here are some elements that make up a positive environment to support learning: Teacher or Mentor Involvement; Available Resources; Comfortable Classroom; Diversity and Inclusion; Motivation and Social Support: Supportive peers, family support, and motivation from the social environment can greatly influence an individual's motivation to learn and achieve their academic or professional goals; Opportunities to Participate; Constructive Feedback; Clear Goals; Freedom and Autonomy; Fair Evaluation and Opportunities for Independent Reading and Learning.